Desain Media Evaluasi Berbasis Wordwall pada Pembelajaran Pendidikan Pancasila - Nababan, Kesnawati; Putera, Rafhi Febryan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop more interactive and interesting learning evaluation media for fourth grade elementary school students in Pancasila Education learning. The evaluation media developed is based on educational games using the wordwall.net platform with the open the box game type. This type of research is research and development with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The data collection techniques used by the researcher are observation, documentation interviews. Researchers can collect data by conducting documentation and direct observation in the field. The resulting data was analyzed descriptively quantitatively. The overall validation results obtained a percentage of 94.8%, of which the validity of the material was 94.28%, the validity of the language was 96%, and the media validation was 94.28%. The results of practicality at the SDN 26 Sungai Nanam test school obtained a percentage of 91.21%. In the first research school at SDN 02 Sungai Nanam obtained a percentage of 93.34% then in the second research school at SDN 18 Sungai Nanam obtained a percentage of 97.71%. The effectiveness of learning media was very successful, as seen from 94.73%, of students in the trial school who achieved learning completeness. For learning completeness, it managed to reach 82.60% in the first research school and 88% in the second research school. Thus, it can be concluded that the Wordwall-based evaluation media in grade IV of Elementary School is declared valid, practical and effective to use.